2004
DOI: 10.1074/jbc.m405538200
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Tumor Necrosis Factor-related Apoptosis-inducing Ligand (TRAIL) Death Receptor Transport to the Cell Surface in Human Colon Cancer Cells Selected for Resistance to TRAIL-induced Apoptosis

Abstract: Many tumor cell types are sensitive to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis. Incubation of TRAIL-sensitive cells with TRAIL invariably leads to resistant survivors even when high doses of TRAIL are used. Because the emergence of resistance to apoptosis is a major concern in successful treatment of cancer, and TRAIL survivors may contribute to therapeutic failure, we investigated potential resistance mechanisms. We selected TRAILresistant SW480 human colon adenocarci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
150
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(164 citation statements)
references
References 34 publications
4
150
3
Order By: Relevance
“…Although evolution of colon carcinoma cells with partially deficient TRAIL-R1 transport to the cell surface has recently been described, this only occurred after long-term culture and clonal selection. 39 By contrast, in our study, TRAIL-resistant cell populations arose rapidly, yet recovered receptor expression following removal of TRAIL. It is possible that high concentrations of TRAIL induce a negative-feedback loop which decreases receptor expression in surviving cells.…”
Section: Discussioncontrasting
confidence: 79%
“…Although evolution of colon carcinoma cells with partially deficient TRAIL-R1 transport to the cell surface has recently been described, this only occurred after long-term culture and clonal selection. 39 By contrast, in our study, TRAIL-resistant cell populations arose rapidly, yet recovered receptor expression following removal of TRAIL. It is possible that high concentrations of TRAIL induce a negative-feedback loop which decreases receptor expression in surviving cells.…”
Section: Discussioncontrasting
confidence: 79%
“…Arsenite also affects cytoskeleton functions and promotes TRAIL-R1/R2 translocation from the intracellular pools to cell surface, as it was observed in the present study. The existence of intracellular pools of TRAIL-R1/R2 and a suppression of receptor translocation in some cancer cell lines have been previously described in several publications [66,67]. Surprisingly, many cell types (both normal and cancer) are relatively resistant to cytotoxic effects of low doses of sodium arsenite, thereby making it possible to use this agent as a regulator of cell signaling pathways in different types of combined treatment.…”
Section: Discussionmentioning
confidence: 94%
“…The importance of examining cell surface expression of TRAIL receptors has been highlighted recently by Jin et al (2004), who showed that TRAIL-resistant variants of the colon carcinoma cell line SW480 had reduced cell surface expression of TRAIL-R1 compared to the parental cell line, although total protein expression remained unchanged. However, it is interesting that in our study the cell surface expression of the four TRAIL receptors did not correlate with the increased sensitivity to TRAIL that is associated with malignancy.…”
Section: Discussionmentioning
confidence: 99%